Ancient microRNA families that regulate transcription factors are preferentially preserved during plant radiation. (1st December 2016) - Shi, Tao; Wang, Kun; Yang, Pingfang
ABSTRACT: Essential genes are usually less likely to be lost during evolution, whereas dispensable genes are lost more frequently. Integrating sacred lotus and other plant microRNA (miRNA) data, we found different ancient miRNA families that arose before eudicot radiation exhibit different evolutionary trajectories. Those ancient miRNA families with higher copy and target numbers, and older age are more likely to be retained in plant descendants and more conserved in (hairpin-structured) miRNA gene sequences. Interestingly, a large portion of the well conserved miRNA families in plant lineages can target transcription factors (TFs). Also, we found miRNA families that target TFs are preferentially retained after sacred lotus genome duplication. In this article, we provide some points to discuss why miRNA families that regulate TFs are more likely to be preserved in plants.